Anticancer Activities of Surfactin and Potential Application of Nanotechnology Assisted Surfactin Delivery - Wu, Yuan-Seng; Ngai, Siew-Ching; Goh, Bey-Hing; Chan, Kok-Gan; Lee, Learn-Han; Chuah, Lay-Hong (Frontiers in Pharmacology, 2017)
Surfactin, a cyclic lipopeptide biosurfactant produced by various strains of Bacillus genus, has been shown to induce cytotoxicity against many cancer types, such as Ehrlich ascites, breast and colon cancers, leukemia and hepatoma. Surfactin treatment can inhibit cancer progression by growth inhibition, cell cycle arrest, apoptosis and metastasis arrest. Owing to the potent effect of surfactin on cancer cells, numerous studies have recently investigated the mechanisms that underlie its anticancer activity. The amphiphilic nature of surfactin allows its easy incorporation nano-formulations, such as polymeric nanoparticles, micelles, microemulsions, liposomes, to name a few. The use of nano-formulations offers the advantage of optimizing surfactin delivery for an improved anticancer therapy. This review focuses on the current knowledge of surfactin properties and biosynthesis; anticancer activity against different cancer models and the underlying mechanisms involved; as well as the potential application of nano-formulations for optimal surfactin delivery.